(untitled) (Research, Society and Development, 2025)
This integrative review aims to examine the role of local governance in addressing the COVID-19 pandemic across diverse countries. Based on 39 scientific articles published between 2020 and April 2025 in the following databases: PubMed, Web of Science, Scopus, Science Direct, and Google Scholar. Findings reveal that the effectiveness of public health crisis responses was intrinsically linked to local governments’ adaptive capacity, intergovernmental coordination, and social participation. Six key thematic categories were identified: (i) adaptive capacity and resilience; (ii) coordination structures; (iii) enabling factors (resources, leadership); (iv) structural challenges (fragmentation, underfunding); (v) social participation; and (vi) contextual variations. Countries such as China, South Korea, and Bangladesh demonstrated effective local-community articulation, whereas Brazil, Sweden, and Zimbabwe faced limitations due to centralization and federative weaknesses. The study concludes that decision-making autonomy, adequate funding, and multi-level cooperation are critical for effective responses to health crises. It recommends strengthening local institutional arrangements for future emergencies. As one of the pioneering multinational comparative analyses of local governance during COVID-19, this review provides an analytical framework applicable to future health crises, offering practical insights for designing resilient decentralized governance systems.